Intercomparison on the measurement of the thoron exhalation rate from building materials. (March 2021) - de With, G.; Kovács, T.; Csordás, A.; Tschiersch, J.; Yang, J.; Sadler, S.W.; Meisenberg, O.
Abstract: Thoron ( 220 Rn) exhalation from building materials has become increasingly recognized as a potential source for radiation exposure in dwellings. However, contrary to radon ( 222 Rn), limited information on thoron exposure is available. As a result no harmonized test procedures for determining thoron exhalation from building materials are available at present. This study is a first interlaboratory comparison of different test methods to determine the thoron exhalation and a pre-step to a harmonized standard. The purpose of this study is to compare the experimental findings from a set of three building materials that are tested, and to identify future challenges in the development of a harmonized standard. Highlights: The intercomparison on thoron exhalation demonstrated considerable variation. A harmonized standard for determining the thoron exhalation would be much welcomed. Suggestions for a harmonized determination of the thoron exhalation are provided.